2019
DOI: 10.1111/hex.12941
|View full text |Cite
|
Sign up to set email alerts
|

Assessing decision regret in caregivers of deceased German people with cancer—A psychometric validation of the Decision Regret Scale for Caregivers

Abstract: Background Decisional regret during or after medical treatments is linked to significant distress. Regret affects not only patients but also caregivers having an active or passive role during decision making. The Decision Regret Scale (DRS) is a self‐report measure for regret in patients after treatment decisions. However, practical and psychometrically robust instruments assessing regret in caregivers are lacking. Objective To develop and validate a caregiver version of the DRS (Decision Regret Scale for Care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 51 publications
(111 reference statements)
1
23
0
Order By: Relevance
“…Joseph-Williams et al (2010) also indicated that Items 2 and 4 focusing on different targets of the regret concept might affect the structure of the DRS. Though limited, the evidence of inconsistencies in measuring decisional regret when using the DRS was also reported by another study (Haun et al, 2019). Additionally, reversed wording might be another reason that affected the construct of the DRS.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Joseph-Williams et al (2010) also indicated that Items 2 and 4 focusing on different targets of the regret concept might affect the structure of the DRS. Though limited, the evidence of inconsistencies in measuring decisional regret when using the DRS was also reported by another study (Haun et al, 2019). Additionally, reversed wording might be another reason that affected the construct of the DRS.…”
Section: Discussionmentioning
confidence: 83%
“…The previous findings regarding the reproducibility of measuring regret are mixed. Haun et al (2019) indicated that the reproducibility of DRS was good for caregivers when using an average time interval of 12 weeks. However, another study showed that patients usually change their attitudes toward the original medical decisions (Becerra Pérez et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 27 The scale has been validated in both adult oncology patients and their caregivers. 28 Acculturation was assessed using the Short Acculturation Scale for Hispanics, which evaluates factors of language use, media, and social relations among Hispanic individuals, 18 with scores ranging from 12 to 60 (lower scores indicating lower levels of acculturation). The NVS and the Short Acculturation Scale for Hispanics were validated in English and Spanish.…”
Section: Methodsmentioning
confidence: 99%
“…In doing so, providers will not only account for the current body of evidence but also prepare the ground for a true shared decision-making process. Finally, with existing studies underscoring the feasibility of interventional trials in the context of OPS, clinical researchers should initiate well-designed and sufficiently powered RCTs accounting for patient and caregiver outcomes [ 10 ]. The worst-case scenario would be the expectable increase of OPS use without reliable evidence on its effects.…”
mentioning
confidence: 99%